2006
DOI: 10.1037/0090-5550.51.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Cultural considerations when providing rehabilitation services to American Indians.

Abstract: American Indians make up a small percentage of the U.S. population but reside in all states and territories and in all major cities. It is critical for rehabilitation psychologists to have an understanding of the unique cultural and ethnic issues associated with service provision to American Indian clientele. Considerations to be taken into account when providing culturally competent care to American Indians include general knowledge about sociopolitical history and current demographics, acculturation and raci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…Our findings are consistent with the literature on delivering culturally appropriate AT services ( Chino & DeBruyn, 2006 ; Lomay & Hinkelbein, 2006 ). Participants in our study highlighted the importance of being “known,” and identified culturally congruent elements of AT service provision that would promote effective AT use by Navajo individuals with disabilities: communication in native language and dialect, access to traditional medicine, consistent medical personnel, education delivered in various formats, in-context training, and inclusion of both client and caregiver opinions in AT device selection.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with the literature on delivering culturally appropriate AT services ( Chino & DeBruyn, 2006 ; Lomay & Hinkelbein, 2006 ). Participants in our study highlighted the importance of being “known,” and identified culturally congruent elements of AT service provision that would promote effective AT use by Navajo individuals with disabilities: communication in native language and dialect, access to traditional medicine, consistent medical personnel, education delivered in various formats, in-context training, and inclusion of both client and caregiver opinions in AT device selection.…”
Section: Discussionsupporting
confidence: 92%
“…We know little about the availability of devices and services within the NN, about whether individuals with disabilities know what exists, about best practices, and about the quality and appropriateness of devices and services as perceived by AT users. Several reviews have included Navajo individuals with disabilities in larger American Indian population studies to understand disability and assess health care needs ( Waldman, Perlman, & Kucine, 2006 ; Wall & Walz, 2003 ), with a focus on education, vocational rehabilitation, and independent living ( Kauffman et al, 2003 ; Wall & Walz); strategies to promote more culturally appropriate rehabilitation and health care for American Indians with disabilities ( Chino & DeBruyn, 2006 ; Lomay & Hinkelbein, 2006 ); or policy for individuals with disabilities ( Dwyer, Fowler, Seekins, Locust, & Clay, 2000 ; Manson & Buchwald, 2007 ; Native American Disability Law Center [NCLC], 2007 ). Other studies have focused on factors contributing to vocational rehabilitation outcomes ( Guy, 2009 ) and independent activity functioning in Navajo elderly ( Fitzpatrick, Alemán, & Van Tran, 2008 ).…”
Section: Navajo Nationmentioning
confidence: 99%
“…As Ripat et al, [6] state that people who live in individualist societies (such as the UK) are characterised as gaining mastery, control, self-sufficiency and predominantly independence. Whereas, people from collectivist societies are more focused on developing social relationships, community, sense of belonging and interdependence [59,60]. Furthermore, Norman [61] points out that in the individuals of collectivist societies (Japan), prefer the aesthetics and beauty of products rather than usability when compared to individualist societies (Israel).…”
Section: Product Semantics and Assistive Technologymentioning
confidence: 99%
“…Inequalities in education, employment, funding, nutrition, political representation, and poverty levels have resulted in marginalization and lack of access to essential health services (Jones, 2006). Additional geographic, financial, and cultural barriers have further decreased access to health care services by AI/AN communities (Lomay & Hinkebein, 2006).…”
Section: American Indian/alaska Native Populations and Fqhcsmentioning
confidence: 99%
“…Multiple studies have identified the largest obstacle to receiving all needed services and achieving a benefit from those services as the misalignment between AI/AN cultural values and traditional service delivery methods (Clark & Kelley, 1992;Lomay & Hinkebein, 2006). In 1992, Clark and Kelley stated, "It is paramount that attention be paid to the underlying values of Native American clients if rehabilitation goals are to be met" (p. 23).…”
Section: American Indian/alaska Native Populations and Fqhcsmentioning
confidence: 99%